Efficient Transformation of Aspergillus nidulans by Electroporation of Germinated Conidia - Olivia Sánchez; Jesús Aguirre (Fungal Genetics Reports, 1996)
We report the transformation of swollen A. nidulans conidia by electroporation. With this method, transformation frequencies were similar to those obtained by using protoplast fusion. The methodology employed is simple, requiring no enzymes nor osmotic stabilizers. The effects of conidial age, DNA topology/concentration and electric field strength are presented